Pengelolaan Sampah di Pantai Wisata Bahari Desa Jawai Laut Kecamatan Jawai Selatan Kabupaten Sambas - Saputra, Mulpi Iman; Nurhaban, Nurhaban; Dwiana, Nida; Nuriza, Nuriza; Saifullah, Saifullah; Agam, Beryaldi; Merdekawati, Dewi; S, Indra Mahyudi; Maryono, Maryono; Yunita, Nurul Fatimah; Jordi, Jordi; Urabi, Debby; Haq, Izhar Amirul (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Marine Tourism Beach in Jawai Laut Village, Sambas Regency, has great potential as a community-based tourism destination. However, the increasing number of tourist visits has caused environmental problems, especially in terms of waste management, especially plastic waste. Lack of facilities, low public and tourist awareness, and lack of external support are the main obstacles in creating a clean and sustainable tourism environment. This community service activity aims to evaluate the condition of waste management, identify the obstacles faced, and formulate strategic solutions. The methods used include field observation, interviews with the community and Pokdarwis, and visual documentation. The results show that despite community efforts to maintain cleanliness, the waste management system has not been running optimally. Therefore, the solutions offered include the application of the 3R principle (Reduce, Reuse, Recycle), increasing environmental education, providing adequate cleaning facilities, utilizing digital media and influencers for campaigns, and implementing a waste sorting system from the source. It is hoped that this strategy can encourage the creation of clean, healthy, and sustainable tourist destinations.